Physician understanding and preferences on the current management and treatment approaches for chronic constipation: a cross-sectional survey-based study - Chatterjee, Kaushik; Nath, Mandovi (International Journal of Research in Medical Sciences, 2022)
Background: Chronic constipation is a prevalent gastrointestinal (GI) motility disorder. To date, there is a lack of real-world evidence on the current treatment approaches and patterns in the management of chronic constipation in India. Methods: We administered a cross-sectional, physical and digital-based survey between May 2021 and November 2021 to experienced gastroenterologists from different zones of India whose practices encompass direct care of patients with chronic constipation. The questionnaire included 30 close-ended questions on qualitative aspects of constipation management, with specific focus on physicians’ experience with efficacy, tolerability and compliance of Duphalac bulk, a combination of soluble fibers and lactulose. Responses of survey participants were summarized and analyzed using descriptive statistics. All analyses were performed using SPSS 25.0. Results: The survey was completed by 195 respondents, of which, 81.5% of physicians preferred osmotic laxatives plus fibers for the management of chronic constipation. Soluble fibers are the preferred choice of physicians (84.6%) over insoluble fibers and lactulose plus soluble fibers was the most preferred in the management of constipation symptoms. The efficacy, tolerability and compliance of Duphalac® bulk were found to be highly satisfactory. Conclusions: In this survey, key practice-relevant information on the current treatment approaches related to the management of chronic constipation from Indian were garnered. The use of soluble fibers was found to be preferred over insoluble fibers, and the clinical profile of a combination formulation of soluble fibers and lactulose was found to be extremely satisfactory among the survey population.